Getting Past the Gateway: An Exploratory Case on Using Utilitarian Scientific Literacy to Support First-Year Students At-Risk of Leaving STEM - Brittany Chambers; Amy Salter; Lycurgus Muldrow (MDPI AG, 2019)
First-year students who enter college pursuing a STEM degree still face challenges persisting through the STEM pipeline (Chen, 2013; Leu, 2017). In this case study, researchers examine the impact of a utilitarian scientific literacy based academic intervention on retention of first-year students in STEM using a mixed methods approach. A sample (n = 116) of first-year students identified as at-risk of not persisting in STEM were enrolled in a for credit utilitarian scientific literacy course. Participants of the semester long course were then compared with a control group of first-year students identified as at-risk of persisting in STEM. A two-proportion z test was performed to assess the mean differences between students and participants of the course were given a survey to gauge student experiences. Quantitative results (φ 0.34, p < 0.05) indicate that the utilitarian scientific literacy course had a statistically significant impact on retention among first-year students at-risk of persisting in STEM. Moreover, qualitative data obtained from participant responses describe internal and external growth as positive outcomes associated with the intervention.